MEKANISME IDEAL PENYELESAIAN SENGKETA ADAT SESUAI DENGAN KONSEP KEKINIAN - i wayan arta ariawan (University of Udayana, 2016)
Based on the data from Bali Regional Police (2014) appear that a lot of custom disputes unfinished effectively thus create some question : (1) what is the factor that influencing effectiveness of solving custom dispute? How is an ideal mechanism for solving custom dispute in Bali according to the contemporary concept? That question is becoming a problem in this script. Since the problem reviewed normatively, indentified some factors that influencing not effectively solving custom dispute, there are (a) law factor that not sufficient yet. (b) law implementer factor with a weak skill and quality in solving the custom dispute.; (c) the supporting of tool and facility factor is not sufficient yet; and (d) society factor who is ignoring the values of custom law; (e) value of society cultures that start shifting, leaving togetherness and glorifying individualistic. About an ideal mechanism for solving accustom dispute in Bali according to contemporary concept, result of the solution conclude that the most accurate of solving custom dispute through internal mechanism based on local wisdom. But, if an internal mechanism failed, then solving of custom dispute can do by using an external mechanism, that is solving of custom dispute which doing by Government with forward an exist custom regulation and /or social regulation and the existence of all is recognized. In the case of this mechanism failed, then conflict solution done by the unit of solving social conflict task that established by government. Disahkannya Undang-Undang RI Nomor 7 Tahun 2012 tentang Penanganan konflik sosial, adalah sebagai upaya pemerintah dalam rangka menyelesaikan sengketa adat secara terpadu dan terintegrasi dalam wadah satuan tugas terpadu. Namun, hasil penelitian menunjukkan bahwa tim terpadu belum berperan maksimal dalam penyelesaian sengketa adat di Bali. Penelitian ini menggunakan metode penelitian hukum empiris bersifat deskriptif. Jenis data primer dan data sekunder, selanjutnya diolah dengan teknik pengolahan data kualitatif, dan dianalisis, mengacu pada asas-asas hukum adat, teori hegemoni, pendapat para sarjana dan berdasarkan peraturan perundang-undangan khususnya Undang-undang No. 7 tahun 2012 tentang Penanganan konflik sosial. Keseluruhan hasil penelitian disajikan secara deskriptif analitis, dengan 2 (dua) rumusan permasalahan yaitu, bagaimanakah mekanisme yang ideal penyelesaian sengketa adat sesuai dengan konsep kekinian, dan apakah faktor-faktor yang mempengaruhi penyelesaian sengketa adat di Bali.